Solar Powered Putu Mayam Machine: Design and Development of a Prototype Machine - Mohd Rizal, Mohamad Alif Hakimi; Zulkifli, Muhammad Akhtar; Mohamad, Mahmod Abd Hakim; Onn, Nurfarahin (Multidisciplinary Applied Research and Innovation, 2025)
This paper presents the design and development of a solar-powered machine to automate putu mayam production, a staple Malaysian kuih dish. Traditional manual methods are labor-intensive, especially for small-scale street vendors, leading to limited production capacity. To address this, a prototype was developed using SolidWorks 2023, featuring aluminum components, a 24V DC motor, and a solar panel system for sustainability. During testing, the machine demonstrated the capability to produce 8 putu mayam units in 10 seconds, a significant improvement over manual production speeds, which averaged 3 seconds per unit. This innovation reduces labor needs by an estimated 67%, enhancing efficiency and providing an affordable solution for small vendors. The solar-powered machine’s integration of mechanical and electrical components represents a step forward in sustainable food processing technology, with the potential to increase production capacity and maintain traditional quality standards.